Paediatric and adult soft tissue sarcomas with NTRK1 gene fusions: a subset of spindle cell sarcomas unified by a prominent myopericytic/haemangiopericytic pattern. Issue 5 (April 2016) - Haller, Florian; Knopf, Jasmin; Ackermann, Anne; Bieg, Matthias; Kleinheinz, Kortine; Schlesner, Matthias; Moskalev, Evgeny A; Will, Rainer; Satir, Ali Abdel; Abdelmagid, Ibtihalat E; Giedl, Johannes; Carbon, Roman; et al.
Abstract: Neoplasms with a myopericytomatous pattern represent a morphological spectrum of lesions encompassing myopericytoma of the skin and soft tissue, angioleiomyoma, myofibromatosis/infantile haemangiopericytoma and putative neoplasms reported as malignant myopericytoma. Lack of reproducible phenotypic and genetic features of malignant myopericytic neoplasms have prevented the establishment of myopericytic sarcoma as an acceptable diagnostic category. Following detection of a LMNA–NTRK1 gene fusion in an index case of paediatric haemangiopericytoma‐like sarcoma by combined whole‐genome and RNA sequencing, we identified three additional sarcomas harbouring NTRK1 gene fusions, termed 'spindle cell sarcoma, NOS with myo/haemangiopericytic growth pattern'. The patients were two children aged 11 months and 2 years and two adults aged 51 and 80 years. While the tumours of the adults were strikingly myopericytoma‐like, but with clear‐cut atypical features, the paediatric cases were more akin to infantile myofibromatosis/haemangiopericytoma. All cases contained numerous thick‐walled dysplastic‐like vessels with segmental or diffuse nodular myxohyaline myo‐intimal proliferations of smooth muscle actin‐positive cells, occasionally associated with thrombosis. Immunohistochemistry showed variable expression of smooth muscle actin and CD34, but other mesenchymal markers, including STAT6, were negative. This study showed a novel variant of myo/haemangiopericytic sarcoma with recurrent NTRK1 gene fusions. Given the recent introduction of a novel therapeutic approach targeting NTRK fusion‐positive neoplasms, recognition of this rare but likely under‐reported sarcoma variant is strongly encouraged. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.